Українська греко-католицька церква у національному примиренні українців і поляків. Минуле та сьогодення. - Рудянин, Іван Петрович; Rudyanin, Ivan (Український Католицький університет, 2008)
Стаття висвітлює участь української греко-католицької церкви в українсько-польських взаєминах. Метою дослідження є висвітлення діяльності церкви у справі примиренні сторін In the article the role of Greek-Catholic church in the relations of polish and Ukrainians is light up. The subject-matter of investigation is the role of Greek-Catholic church in reconciliation of Ukrainian and Polish nations.
Keywords: церква; духовенство; примирення; конфлікт; Григорій Яхимович; Андрей Шептицький; Любомир Гузар; church; clergy; reconciliation; conflict; Grirorij Yakhumovuch; Andrej Scheptutzkyi; Lubomur Guzar